Respuesta :

Answer:

t = 3

Step-by-step explanation:

area of a right angled triangle

formula :

[tex]\frac{1}{2} * base * height[/tex]

by looking at the picture we can notice that there is one big triangle that includes the entire base ( unlabeled length and 4 yd) -this is triangle 1

the triangle which already has the area is regarded as-- triangle 2

the triangle which is unknown and has height (t) is -- triangle 3

from this we can create a formula :

triangle 1 - triangle 2 = triangle 3

lets put in the values

[tex]\frac{1}{2} * (x+4) * t[/tex]  -  [tex]6 = \frac{1}{2} * x * t[/tex]

Note : i am using (x) as the unknown length of the base excluding the 4yrd

[tex]\frac{1}{2}xt + 2t -6 = \frac{1}{2}xt[/tex]

[tex]\frac{1}{2}xt +2t - 6 - \frac{1}{2}xt[/tex]

2t - 6 = 0

2t = 6

t = 3

ACCESS MORE